Corozal Bay showing entrance to Corozal Town - Government Information Service (The Angelus Press, Belize City, British Honduras, C.A. Printed in U.S.A., 2009)
Coastal shoreline, Belize, lined with coconut trees and houses.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Belize; Seashore--Belize; Coconut palm--Belize; Dwellings--Belize